2009
DOI: 10.1111/j.1741-4369.2009.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

In defence of writing: a social semiotic perspective on digital media, literacy and learning

Abstract: From a learning perspective, social semiotics researchers tend to focus on the liberation latent in the multimedia options available through the new media. It is true that digital media democratise the possibilities open to the general public of a more varied and comprehensive text production than ever before, both in and outside school. Participating in this text production naturally implies a richer potential for learning. But digital technology also allows us to opt out of, and thus avoid, semiotic work. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The evidence from our first task was that children's selection of stories from their media experiences encouraged less well-developed narratives. This does not, however, lead us to concur with Skaar's (2009) conclusion in his analysis of the learning involved in children's digital story making, that the incorporation of image is a less demanding and therefore, by implication, a less worthwhile experience of meaning-making than a composition in words. Rather, it leads us to suggest that what teachers need to focus on is the selection of appropriate semiotic tools for particular tasks.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The evidence from our first task was that children's selection of stories from their media experiences encouraged less well-developed narratives. This does not, however, lead us to concur with Skaar's (2009) conclusion in his analysis of the learning involved in children's digital story making, that the incorporation of image is a less demanding and therefore, by implication, a less worthwhile experience of meaning-making than a composition in words. Rather, it leads us to suggest that what teachers need to focus on is the selection of appropriate semiotic tools for particular tasks.…”
Section: Discussionmentioning
confidence: 60%
“…Researchers have shown that the narrative elements of popular culture have great power to capture children's interest and inform their understanding of character and action in their interactive play leading to engaged oral and written work (Dyson 2003;Marsh and Millard, 2005;Marsh, 2005Marsh, , 2008Marsh, , 2010Willet, 2005Willet, , 2009. Dependence on popular culture as a model for writing, however, has been shown to limit the scope of young writers' use of language and in particular, the development of inner thought and feeling (Millard, 1997, Skaar, 2009). Because of this, I have argued for a pedagogy that would enable the fusion of children's popular fictions with traditional elements of narrative and creative writing.…”
Section: Background To the Studymentioning
confidence: 99%
“…Such a finding is important because it adds weight to a strand in the debate about blog use in education that cites their unimportance to learners and their superficial and uncritical content as unsuited to the analysis and synthesis typically associated with school learning tasks (Bennett & Maton, 2010). The lack of attention to blog postings could also lend support to Skaar's (2009) concern that multimedia projects detract from semiotic tasks associated with the construction of detailed, connected texts that show understanding or a point of view on a particular topic and the view that blogging does not engage students with learning (Halic et al, 2010). However, these findings need to be contextualized by other data from the project related to participant interaction.…”
Section: Instances Of Peer Commentsmentioning
confidence: 84%
“…One of the starting points for this paper was to seek for a conceptual viewpoint that united the initial separated learning and technological backgrounds. An interesting approach that looks simultaneously at learning and use of technology is Social Semiotics (Skaar 2009), which describes the connections between learning and the use of technology. First, learning is seen as taking place through the semiotic work performed with created signs and texts.…”
Section: Towards a Semiotic Viewmentioning
confidence: 99%